The influence of international firms semiotic advertising efficacy on Gen-Y brand equity and purchase intent of smart phones - Adaobi, Oputa Elizabeth (2018)
The objective of this research is to demonstrate the influence of semiotic advertising efficacy on Generation Y’s brand equity and purchase intention towards smartphone. Semiotic advertising is an effective, modern approach to advertising that focuses on the use of different signs, symbols, images and other visual aids for the purpose of marketing a given product or service. Since these signs tend to create an image of the brand in consumers’ mind and also demonstrates the brand association with their cultural orientation, beliefs and values, semiotic advertising is said to have a significant impact on the brand equity as perceived by Generation Y consumers. This study also assumes that brand equity, based on its components of perception, recognition, parity, loyalty and trust positively influences Generation Y’s purchase intentions towards smartphone. In addition, semiotic advertising is also expected to have a positive influence on buyer’s purchase intention. Data for this research were collected from 620 Generation Y smart phone users using a survey method, based on the semiotic advertising of four main smartphone brands namely Oppo, Samsung, iPhone and Lenovo. The survey instruments were self-developed by the researcher to measure semiotic advertising efficacy, brand equity and purchase intentions as perceived towards advertisements of four smart phones shown to the respondents while undertaking the survey. Surveys were distributed to Generation Y in three main states in Malaysia namely Kuala Lumpur, Johor and Kedah. It is hence concluded from the findings that the Generation Y’s purchase intentions towards smartphone increase when the efficacy of semiotic advertising increases. Thus, firms need to ensure that the visual elements and semiotics used in their brand advertisements align with the cultural characteristics of buyers in order to enhance their overall efficacy.